Transient complete heart block following catheter ablation of a left lateral accessory pathway. Issue 1 (3rd November 2018) - Schweis, Franz; Ho, Gordon; Krummen, David E.; Hoffmayer, Kurt; Birgersdotter‐Green, Ulrika; Feld, Gregory
Abstract: A 16‐year‐old female with symptomatic Wolff‐Parkinson‐White (WPW) syndrome underwent catheter ablation of a left‐sided lateral accessory pathway. The accessory pathway was eliminated with the first ablation lesion; however, the patient immediately developed complete heart block (CHB). At first, complete heart block was thought to be due to ablation of left atrial extension of the AV node, and pacemaker therapy was considered. However, careful ECG analysis revealed that the development of CHB was in fact due to bump injury to the AV node during transseptal catheterization. Conservative management allowed resolution of AV nodal conduction without need for a permanent pacemaker.